Cooperative Training Program and Member Satisfaction in Calamba City, Laguna, Philippines - Debasa , Annieleah (Journal of Interdisciplinary Perspectives, 2024)
Implementing a training program was a practical relief for the government to eradicate the effect of modern economic scale on marginalized business communities like cooperatives. This study evaluated the effectiveness of the Cooperative Training Program in Calamba City, providing insights into its impact on micro and small cooperative enterprises. It offered detailed feedback on member satisfaction and program outcomes, which can guide necessary improvements to meet participants' needs better. The research utilized a descriptive design and surveyed 14 CLDD employees and 64 Cooperative members operating in Calamba City through a stratified random sampling technique. Specifically, all regular employees of CLDD and Cooperative members from micro-scaled cooperative enterprises who had received the training program were selected as the research sample. Data were collected using Australian Government Standards for a community-based training program called AQTF Survey Form 2007 based on the Quality Indicator Reporting Requirements (2021) and analyzed through statistical treatments, including the simple mean, four-point Likert scale, standard deviation, and Pearson correlation coefficient. The findings show that the CLDD training program was fully implemented, with no notable difference in how CLDD employees and cooperative members rated its execution. Cooperative members expressed high satisfaction with the training, and there was a strong link between how well the program was implemented and their satisfaction levels. In line with these results, the research proposed an enhancement program to improve key areas of the current CLDD training program implementation: training resources, trainer quality, potential and service quality, and product enhancement. The goal is to enhance the overall program and increase satisfaction among cooperative members.